Penggunaan Aplikasi Android Dengan Inspring Suite 10 Dalam Pembelajaran Pendidikan Agama Islam - Munawaroh, Nenden; Ainissyifa, Hilda; ijudin, ijudin; Rahmat, Acep; Nurdiansyah, Ilham; anton, anton (Universitas Garut, 2024)
Abstract In the current digital era, the use of technology has become a necessity in the learning process. One technology that can be utilized is the Android application, which can be an interactive and interesting tool for teachers in teaching in the era of digitalization. The Inspiring Suite 10 application is oriented towards education and programming which must be integrated with creative and relevant content. This service activity aims to improve the understanding and skills of teachers at SMPIT Ash-shidiqiyyah to explore the use of Android applications using Inspiring Suite 10 in PAI learning. The service method is carried out through several stages starting from the Introduction (Preliminary Study), Development of Training Materials, Participatory Approach, Initial and Final Training and Evaluation. Participants involved in the learning process with this application are 35 teachers at Asshiddiqiyah Middle School. Results of the activity This service shows an increase in teachers' understanding and skills in using the Android application with Inspiring Suite 10 in PAI learning which makes a positive contribution in increasing interest in learning, understanding of the material, and interaction between teachers and students. This application provides various features that support interactive learning, such as interactive learning modules, interactive question banks, and discussion forums for sharing experiences and understanding. Pretest and Posttest results show an increase in teachers' skills with an average Pretest result of 6.64 while an average Posttest result of 14.76. Keyword: Andriod application; Ispring suite 10; PAI Learning. Abstrak Dalam era digital saat ini, penggunaan teknologi telah menjadi sebuah keharusan dalam proses pembelajaran. Salah satu teknologi yang dapat dimanfaatkan adalah aplikasi Android, yang dapat menjadi sarana interaktif dan menarik bagi para guru dalam mengajar pada era digitalisasi. Aplikasi Inspiring Suite 10 berorientasi pada pendidikan dan pemrograman yang harus diintegrasikan dengan konten yang kreatif dan relevan. Kegiatan pengabdian ini bertujuan untuk meningkatkan pemahaman dan keterampilan para guru di SMPIT Ash-shidiqiyyah untuk mengeksplorasi penggunaan aplikasi Android dengan menggunakan Inspiring Suite 10 dalam pembelajaran PAI. Metode pengabdian yang dilakukan melalui beberapa tahapan mulai dari Pendahuluan (Preliminary Study), Pengembangan Materi Pelatihan, Pendekatan Partisipatif, Pelatihan dan Evaluasi Awal dan Akhir partisipan yang terlibat dalam proses pembelajaran dengan aplikasi tersebut yaitu para guru di SMP Asshiddiqiyah yang berjumlah 35 orang. Hasil kegiatan pengabdian ini menunjukkan peningkatan pemahaman dan keterampilan para guru dalam penggunaan aplikasi Android dengan Inspiring Suite 10 pada pembelajaran PAI memberikan kontribusi positif dalam meningkatkan minat belajar, pemahaman materi, dan interaksi antara guru dan siswa. Aplikasi ini menyediakan berbagai fitur yang mendukung pembelajaran interaktif, seperti modul pembelajaran interaktif, bank soal interaktif, serta forum diskusi untuk berbagi pengalaman dan pemahaman. Hasil Pretest dan Postest menunjukan peningkatan keterampilan para guru dengan rata hasil Pretest 6.64 sedangkan hasil Postest rata-rata 14,76. Kata-kata kunci: Aplikasi Andriod; Ispring suite 10; Pembelajaran PAI